Can Critical Thinking Be Learned? Critical Examination of Critical Thinking - Smokrović, Nenad (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
The goal of this paper is to analyse the phenomenon of critical thinking and to examine the question of acquiring knowledge or the possibility to learn critical thinking. In particular, we want to examine which aspect(s) or element(s) of this phenomenon are subject to teaching and learning and which can at best be only slightly improved. In contrast to the unspecific and indiscriminate general view that critical thinking can be learned by nearly everyone, we argue that the answer depends on what is considered to be the nature and structure of critical thinking. In contrast to a more elaborate view that distinguishes two general parts of good reasoning, logical skills understood as the core of critical thinking, and intellectual virtues, and argues that only the former but not the latter can be subject to pedagogical teaching, we argue for the exact opposite.